Learning Arabic Through Durusullughoh at Assalam Mosque Surabaya: Belajar Bahasa Arab Melalui Durusullughoh di Masjid Assalam Surabaya - Ma’arif, Arda Ryvaldo Roizya; Ammar Lc., MA , Farikh Marzuki (Indonesian Journal of Islamic Studies, 2025)
General Background: Arabic is a fundamental language in Islamic scholarship and religious practice, serving as the linguistic medium of the Qur’an and classical Islamic sciences. Specific Background: However, the challenge of learning Arabic among non-native speakers, particularly in informal educational settings such as mosques, remains significant. Knowledge Gap: Few studies have investigated how structured Arabic learning using classical texts operates in community-based environments. Aims: This study explores the learning process, supporting and inhibiting factors of Arabic language instruction using Durusullughoh Al Arobiyyah Lighoiri Nathiqina Biha at the Assalam Puri Mas Mosque, Surabaya. Results: Findings reveal that the program follows a weekly schedule emphasizing practical exercises over theoretical content. Supporting factors include accessible learning materials, conducive facilities, and institutional support, while challenges stem from low learner motivation, scheduling constraints, and lack of formal commitment. Novelty: This research offers empirical evidence of mosque-based Arabic learning dynamics through Durusullughoh as an effective entry-level text for non-native learners. Implications: The study underscores the potential of integrating structured Arabic instruction within mosque environments to promote sustainable Islamic education beyond formal schooling. Highlights: Weekly mosque-based Arabic learning emphasizes practical use. Balanced view of supporting and inhibiting learning factors. Promotes mosque as a sustainable hub for Islamic language education. Keywords: Arabic Learning, Mosque Education, Durusullughoh, Islamic Pedagogy, Language Practice